Penerapan Augmented Reality sebagai Media Pembelajaran Perubahan Wujud Benda untuk Sekolah Dasar Berbasis Android - Budy Putri, Raden Neomy Lusie Ratna Deseina; Prasetyo, Novian Adi; Wahyuningrum, Tenia (Institut Teknologi Telkom Purwokerto, 2023)
The COVID 19 outbreak has had a tremendous impact. In Indonesia in the education sector, face-to-face learning in the classroom is replaced by online learning by utilizing internet applications and technology. With such sudden changes in learning methods, UNICEF Indonesia and the Ministry of Religious Affairs of the Republic of Indonesia conducted a survey on the level of development and satisfaction in learning, and the results in elementary school learning are very many children who find it difficult to learn and understand the material, especially materials that require time, practice and reasoning, as well as material Changes in The Form of Objects in the subjects of Natural Sciences Elementary School Third grade. With such case studies, the authors provide solutions by providing more interesting and easy-to-understand learning methods, namely using the concept of Augmented Reality. This android-based Perwuda CPG app combines the concept of markers in the form of picture cards with Augmented Reality apps. Markers contained on the picture card will be captured by the camera from the smartphone device and then processed to bring up 3D objects and some 3D objects that have been animated from changes in the shape of objects on the layer in realtime. The results of this Perwuda CPG trial on several types of smartphones show that all functions in the Application are running well. Then for user satisfaction researchers use heuristic evaluation method with 10 heuristics to three expert usability evaluators. There are 30 questions for each evaluator, in evaluating the application evaluators find problems, but the problem is found by some evaluators only, where the first evaluator finds 17 problems, the second evaluator finds 6 problems, the third evaluator finds 12 problems. The results of each evaluator in the number and in average so as to produce the highest severity rating for CPG application problems that is in visibility of system status with an average number of values - average value of 1.22, and severity rating is the lowest consistency and standards with an average number - average value of 0.22